Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Universal School Meals During the Pandemic: A Mixed Methods Analysis of Parent Perceptions From California and Maine - Leah Elizabeth Chapman; Wendi Gosliner; Deborah A. Olarte; Lorrene D. Ritchie; Marlene B. Schwartz; Michele Polacsek; Christina E. Hecht; Kenneth Hecht; Lindsey Turner; Anisha I. Patel; Monica Daniela Zuercher; Margaret Read; et al. (Journal of the Academy of Nutrition and Dietetics, 2024)

Dissemination and persistence of antimicrobial resistance (AMR) along the wastewater-river continuum - Daniel S. Read; H. Soon Gweon; Michael J. Bowes; Muna F. Anjum; Derrick W. Crook; Kevin K. Chau; Liam P. Shaw; Alasdair Hubbard; Manal AbuOun; Holly J. Tipper; Sarah J. Hoosdally; Mark J. Bailey; et al. (Water Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Targeting and image acquisition of Martian surface features with TGO/CaSSIS - M. Almeida; M. Read; N. Thomas; G. Cremonese; P. Becerra; G. Borrini; S. Byrne; M. Gruber; R. Heyd; C.M. Marriner; G. McArthur; A.S. McEwen; et al. (Planetary and Space Science, 2023)

Establishing effective conservation management strategies for a poorly known endangered species: a case study using Australia’s Night Parrot (Pezoporus occidentalis) - Nicholas P. Leseberg; Alex Kutt; Megan C. Evans; Tida Nou; Scott Spillias; Zoe Stone; Jessica C. Walsh; Stephen A. Murphy; Mike Bamford; Allan H. Burbidge; Kate Crossing; Robert A. Davis; et al. (Biodiversity and Conservation, 2023)
An evidence-based approach to the conservation management of a species requires knowledge of that species’ status, distribution, ecology, and threats. Coupled with budgets for specific conservation strategies, this knowledge allows prioritisation of funding toward activities that maximise benefit for the species. However, many threatened species are poorly known, and determining which conservation strategies will achieve this is difficult. Such cases require approaches that allow decision-making under uncertainty. Here we used structured expert elicitation to estimate the likely benefit of potential management strategies for the Critically Endangered and, until recently, poorly known Night Parrot ( Pezoporus occidentalis ). Experts considered cat management the single most effective management strategy for the Night Parrot. However, a combination of protecting and actively managing existing intact Night Parrot habitat through management of grazing, controlling feral cats, and managing fire specifically to maintain Night Parrot habitat was thought to result in the greatest conservation gains. The most cost-effective strategies were thought to be fire management to maintain Night Parrot habitat, and intensive cat management using control methods that exploit local knowledge of cat movements and ecology. Protecting and restoring potentially suitable, but degraded, Night Parrot habitat was considered the least effective and least cost-effective strategy. These expert judgements provide an informed starting point for land managers implementing on-ground programs targeting the Night Parrot, and those developing policy aimed at the species’ longer-term conservation. As a set of hypotheses, they should be implemented, assessed, and improved within an adaptive management framework that also considers the likely co-benefits of these strategies for other species and ecosystems. The broader methodology is applicable to conservation planning for the management and conservation of other poorly known threatened species.

A surplus no more? Variation in krill availability impacts reproductive rates of Antarctic baleen whales - Logan J. Pallin; Nick M. Kellar; Debbie Steel; Natalia Botero‐Acosta; C. Scott Baker; Jack A. Conroy; Daniel P. Costa; Chris M. Johnson; David W. Johnston; Ross C. Nichols; Doug P. Nowacek; Andrew J. Read; et al. (Global Change Biology, 2023)
The krill surplus hypothesis of unlimited prey resources available for Antarctic predators due to commercial whaling in the 20th century has remained largely untested since the 1970s. Rapid warming of the Western Antarctic Peninsula (WAP) over the past 50 years has resulted in decreased seasonal ice cover and a reduction of krill. The latter is being exacerbated by a commercial krill fishery in the region. Despite this, humpback whale populations have increased but may be at a threshold for growth based on these human‐induced changes. Understanding how climate‐mediated variation in prey availability influences humpback whale population dynamics is critical for focused management and conservation actions. Using an 8‐year dataset (2013–2020), we show that inter‐annual humpback whale pregnancy rates, as determined from skin‐blubber biopsy samples ( n = 616), are positively correlated with krill availability and fluctuations in ice cover in the previous year. Pregnancy rates showed significant inter‐annual variability, between 29% and 86%. Our results indicate that krill availability is in fact limiting and affecting reproductive rates, in contrast to the krill surplus hypothesis. This suggests that this population of humpback whales may be at a threshold for population growth due to prey limitations. As a result, continued warming and increased fishing along the WAP, which continue to reduce krill stocks, will likely impact this humpback whale population and other krill predators in the region. Humpback whales are sentinel species of ecosystem health, and changes in pregnancy rates can provide quantifiable signals of the impact of environmental change at the population level. Our findings must be considered paramount in developing new and more restrictive conservation and management plans for the Antarctic marine ecosystem and minimizing the negative impacts of human activities in the region.

The impact of temperature at depth on estimates of thermal habitat for short‐finned pilot whales - Stephanie K. Adamczak; William A. McLellan; Andrew J. Read; Christopher L. P. Wolfe; Lesley H. Thorne (Marine Mammal Science, 2021)
Short‐finned pilot whales ( Globicephala macrorhynchus ) experience dramatic changes in temperature during deep dives, but studies of pilot whale habitat use typically rely solely on surface temperature measurements. We quantified vertically integrated thermal habitat for short‐finned pilot whales using a novel metric, degree‐hours, developed using data from digital acoustic recording tags (DTAGs) deployed off Cape Hatteras along with interpolated temperature profiles at depth from the Met Office Hadley Centre EN4 oceanographic data set. We then compared estimates of thermal habitat calculated from surface waters with estimates of vertically integrated thermal habitat calculated using EN4 data collected along the eastern seaboard of the U.S. to understand how available thermal habitat is influenced by seasonal and spatial variability in water temperature. Estimates of vertically integrated thermal habitat were typically lower than estimates produced using surface temperatures, and the difference was greatest at intermediate latitudes and in warmer seasons, where and when there is a high degree of variability between surface and bottom temperatures. Our work highlights the importance of considering temperature at depth to accurately assess the thermal habitat of deep‐diving marine vertebrates, and presents a means of quantifying thermal habitat that will be useful for understanding the thermal ranges of these species.

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Detection of herpesvirus capsids in transmission electron microscopy images using transfer learning - K. Shaga Devan; P. Walther; J. von Einem; T. Ropinski; H. A. Kestler; C. Read (Histochemistry and Cell Biology, 2019)

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

The metabolic regimes of flowing waters - E. S. Bernhardt; J. B. Heffernan; N. B. Grimm; E. H. Stanley; J. W. Harvey; M. Arroita; A. P. Appling; M. J. Cohen; W. H. McDowell; R. O. Hall; J. S. Read; B. J. Roberts; et al. (Limnology and Oceanography, 2018)
The processes and biomass that characterize any ecosystem are fundamentally constrained by the total amount of energy that is either fixed within or delivered across its boundaries. Ultimately, ecosystems may be understood and classified by their rates of total and net productivity and by the seasonal patterns of photosynthesis and respiration. Such understanding is well developed for terrestrial and lentic ecosystems but our understanding of ecosystem phenology has lagged well behind for rivers. The proliferation of reliable and inexpensive sensors for monitoring dissolved oxygen and carbon dioxide is underpinning a revolution in our understanding of the ecosystem energetics of rivers. Here, we synthesize our current understanding of the drivers and constraints on river metabolism, and set out a research agenda aimed at characterizing, classifying and modeling the current and future metabolic regimes of flowing waters.

Temporal stability and mixed-stock analyses of humpback whales (Megaptera novaeangliae) in the nearshore waters of the Western Antarctic Peninsula - G. R. Albertson; A. S. Friedlaender; D. J. Steel; A. Aguayo-Lobo; S. L. Bonatto; S. Caballero; R. Constantine; A. L. Cypriano-Souza; M. H. Engel; C. Garrigue; L. Flórez-González; D. W. Johnston; et al. (Polar Biology, 2018)

Resilience of harbor porpoises to anthropogenic disturbance: Must they really feed continuously? - Jeroen P. A. Hoekendijk; Jerome Spitz; Andrew J. Read; Mardik F. Leopold; Michael C. Fontaine (Marine Mammal Science, 2018)

Arbuscular mycorrhizas are present on Spitsbergen - K. K. Newsham; P. B. Eidesen; M. L. Davey; J. Axelsen; E. Courtecuisse; C. Flintrop; A. G. Johansson; M. Kiepert; S.E. Larsen; K. E. Lorberau; M. Maurset; J. McQuilkin; et al. (Mycorrhiza, 2017)

Ecosystem metabolism in a stratified lake - Peter A. Staehr; Jesper P. A. Christensen; Ryan D. Batt; Jordan S. Read (Limnology and Oceanography, 2012)
Seasonal changes in rates of gross primary production (GPP), net ecosystem production (NEP), and respiration (R) were determined from frequent automated profiles of dissolved oxygen (DO) and temperature in a clear‐water polymictic lake. Metabolic rate calculations were made using a method that integrates rates across the entire depth profile and includes DO exchange between depth layers driven by mixed‐layer deepening and eddy diffusivity. During full mixing, NEP was close to zero throughout the water column, and GPP and R were reduced 2–10 times compared to stratified periods. When present, the metalimnion contributed 21% and 27% to whole‐lake areal rates of GPP and R, respectively. Net autotrophy prevailed in the epilimnion (NEP = 11 ± 14 mmol O 2 m −3 d −1 ; mean ± SD) compared to balanced production in the metalimnion (NEP = 2 ± 19 mmol O 2 m −3 d −1 ) and net heterotrophic conditions in hypolimnic waters (NEP = −15 ± 24 mmol O 2 m −3 d −1 ). Positive NEP occurred in the metalimnion during periods when the photic depth extended below the mixed‐layer depth. Although the single‐sonde method estimated higher areal GPP (19%) and R (14%) compared to the two depth‐integrated approaches, differences were not significant. During stratification, daily variability in epilimnetic DO was dominated by metabolism (46%) and air‐water gas exchange (44%). Fluxes related to mixed‐layer deepening dominated in meta‐ and hypolimnic waters (49% and 64%), while eddy diffusion (1% and 14%) was less important. Although air‐water gas exchange rates differed among the three formulations of gas‐transfer velocity, this had no significant effect on metabolic rates.

Observations of a western North Atlantic right whale ( Eubalaena glacialis ) birth offshore of the protected southeast U.S. critical habitat - H. J. Foley; R. C. Holt; R. E. Hardee; P. B. Nilsson; K. A. Jackson; A. J. Read; D. A. Pabst; W. A. McLellan (Marine Mammal Science, 2011)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

Long-term biomonitoring of lichen and bryophyte biodiversity at Burnham Beeches SAC and global environmental change - O. William Purvis; I. Tittley; P. D. Jim Chimonides; Roger Bamber; Peta A. Hayes; Peter W. James; Fred J. Rumsey; Helen Read (Systematics and Biodiversity, 2010)

Leptotrichia endocarditis: Report of two cases from the International Collaboration on Endocarditis (ICE) database and review of previous cases - L. B. Caram; J. P. Linefsky; K. M. Read; D. R. Murdoch; T. Lalani; C. W. Woods; L. B. Reller; S. S. Kanj; M. M. Premru; S. Ryan; M. Al-Hegelan; P. Y. Donnio; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

The costs of intersexuality: a crustacean perspective - A. T. Ford; T. F. Fernandes; P. A. Read; C. D. Robinson; I. M. Davies (Marine Biology, 2004)

Macrobenthic polychaete assemblages of the continental shelf and upper slope off the west coast of the South Island, New Zealand - P. K. Probert; G. B. Read; S. L. Grove; A. A. Rowden (New Zealand Journal of Marine and Freshwater Research, 2001)
Polychaete assemblages are described from replicate box‐core samples collected in summer 1983 at 18 stations on the continental shelf and upper slope (28–943 m) off the west coast of the South Island, New Zealand, south‐eastern Tasman Sea (c. 41–43°S, 169–172°E). Three main station groupings were identified by multivariate analysis: (1) inner shelf sandy stations characterised by Prionospio australiensis, Aricidea (Acesta) sp., Magelona cf. dakini, Paraprionospio aff. pinnata, Aglaophamus sp., Heteromastus filiformis , and Magelona sp.; (2) middle to outer shelf muddy stations characterised by Levinsenia cf. gracilis, Prionospio australiensis, Paraprionospio coora, Aglaophamus verrilli , and Auchenoplax mesos; and (3) upper slope sandy mud or mud stations characterised by Prionospio ehlersi . A combination of water depth and sediment clay content provided the best correlation with the biotic pattern. Spionidae was the most abundant family (49% of polychaete individuals), which may reflect the scope for opportunistic species in a shelf environment characterised by a high input of terrigenous sediment and episodic upwelling.

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)

Linkage disequilibrium studies in multiple endocrine neoplasia type 1 (MEN1) - J. H. D. Bassett; A. A. J. Pannett; S. A. Forbes; R. V. Thakker; M. McCarthy; A. P. Read; B. T. Teh; C. Larsson; S. Kytl; J. Leisti; P. Salmela; G. Weber; et al. (Human Genetics, 1997)